1988
DOI: 10.1183/09031936.93.01060547
|View full text |Cite
|
Sign up to set email alerts
|

Particle size study of nine metered dose inhalers, and their deposition probabilities in the airways

Abstract: This study deals with the particle size measurement of nine aerosol metered dose inhalers. Calibration was made possible by the use of a laser particle velocimeter (aerodynamic Particle Sizer from TSI). The count median aerodynamic diameters (CMAD) show little variation, from 0.63 to 0.73 micron, with standard deviations (sigma g) between 1.2 and 1.8. Aerodynamic diameter aerosol diagram analysis showed multimodal mass distribution for all the tested dose inhalers. Calculations for the airway deposition probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Unfortunately, it is difficult to determine the exact size of particles released from currently available MDIs, with several studies citing varying results. 36,54 LeBelle et al 55 and Crim et al 56 described sizes between 1.1 and 4.7 μm for cascade impactors, Dolovich 57 reported 0.05-35 μm particle sizes for most inhalers, and two other reports indicated 200 μm as the maximum particle size. 57 Our results indicate that particles 6-10 μm would be ideal for deposition at stenotic regions, thus implying that current inhalers would not deposit drugs effectively in these regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, it is difficult to determine the exact size of particles released from currently available MDIs, with several studies citing varying results. 36,54 LeBelle et al 55 and Crim et al 56 described sizes between 1.1 and 4.7 μm for cascade impactors, Dolovich 57 reported 0.05-35 μm particle sizes for most inhalers, and two other reports indicated 200 μm as the maximum particle size. 57 Our results indicate that particles 6-10 μm would be ideal for deposition at stenotic regions, thus implying that current inhalers would not deposit drugs effectively in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to compare with standard drug particle sizes emitted from common inhalers. Unfortunately, it is difficult to determine the exact size of particles released from currently available MDIs, with several studies citing varying results 36,54 . LeBelle et al 55 and Crim et al 56 described sizes between 1.1 and 4.7 μm for cascade impactors, Dolovich 57 reported 0.05–35 μm particle sizes for most inhalers, and two other reports indicated 200 μm as the maximum particle size 57 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, it is difficult to determine the precise particle size distribution that is emitted by MDIs. 33,34 Nonetheless, LeBelle et al 35 and Crim et al 36 determined the range of particle sizes of MDIs as 1.1 to 4.7 mm using a cascade impactor. LeBelle et al 35 reported the mass median aerodynamic diameter (MMAD) and geometric standard deviation (sg) of 4 inhalers to lie between 2.28 mm (sg = 2.63) and 4.13 mm (sg = 2.19).…”
Section: Discussionmentioning
confidence: 99%